CSC339 - Practical Training / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2022)
Prior to graduation, students need to acquire working experience in an information processing environment. Therefore, this subject will introduce them to the challenging working environment.